PENGARUH KEAHLIAN, TEKANAN KETAATAN, TEKANAN WAKTU TERHADAP KUALITAS AUDIT JUDGMENT DENGAN KOMPLEKSITAS TUGAS SEBAGAI PEMODERASI - Virginia Nirmala, Made Rara; Latrini, Made Yeni (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
Audit judgment is an auditor's judgment response to information affects decision-making documentation evidence and the auditor's opinion on financial statements. The aim research to empirically examine influence of auditor expertise, obedience pressure, and time budget pressure on audit quality judgment by complexity task as moderating variables. The study was conducted on public accounting firm in Bali in 2016. The samples were obtained by 64 auditors. The sampling method using purposive sampling. Data analysis techniques used are moderated regression analysis. The results showed expertise auditors positive effect on audit quality of judgment. Obedience pressure no effect on audit quality of judgment. Time budget pressure negative affect on audit quality of judgment. Task complexity of weakening influence expertise auditor on audit quality of judgment. Task complexity is not able to moderate effect obedience pressure on audit quality of judgment. Task complexity strengthenin influence time budget pressure on audit quality of judgment.
Keywords: audit quality of judgment, expertise auditor, obedience pressure, time budget pressure, and task complexity